Assessing of Graduate Students’ Utilization of AI Tools in Scientific Research A Survey at Tishreen University - مرهج, ماهر (Latakia University Journal - Economic and Legal Sciences Series, 2025)
This research aimed to explore the most important artificial intelligence tools that can be used to enhance researchers' capabilities in scientific research and to examine the reality of their usage by graduate students at Tishreen University. The researcher adopted the experimental approach through testing these tools, and the survey method, organizing a questionnaire distributed to 351 graduate students at Tishreen University. Of these, 342 responses were received, with 128 questionnaires deemed unsuitable for analysis, while the number of valid questionnaires for analysis was 214. The research community consisted of 4,031 graduate students, according to the statistics of the Directorate of Statistics and Planning for the academic year 2022-2023. Appropriate statistical tests, such as the one-sample Student’s t-test, were used, and SPSS was relied upon as a tool for data analysis. The main conclusion was that there are motivations for graduate students to use AI tools due to their ability to search for, summarize, translate, formulate, and extract ideas from scientific articles with high quality. The researcher recommended the need to provide training programs to train students on how to use these tools and how to generate texts from them and rephrase them in the researcher’s own style, along with ensuring the availability of plagiarism detection software capable of identifying AI-generated text.